Immunoinformatics Approach for Multiepitope Vaccine Prediction from H, M, F, and N Proteins of Peste des Petits Ruminants Virus - Bothina B. M. Gaafar; Sumaia A. Ali; Khoubieb Ali Abd-elrahman; Yassir A. Almofti (Journal of Immunology Research)
Background. Small ruminant morbillivirus or peste des petits ruminants virus (PPRV) is an acute and highly contagious viral disease of goats, sheep, and other livestock. This study aimed at predicting an effective multiepitope vaccine against PPRV from the immunogenic proteins haemagglutinin (H), matrix (M), fusion (F), and nucleoprotein (N) using immunoinformatics tools. Materials and Methods. The sequences of the immunogenic proteins were retrieved from GenBank of the National Center for Biotechnology Information (NCBI). BioEdit software was used to align each protein from the retrieved sequences for conservancy. Immune Epitope Database (IEDB) analysis resources were used to predict B and T cell epitopes. For B cells, the criteria for electing epitopes depend on the epitope linearity, surface accessibility, and antigenicity. Results. Nine epitopes from the H protein, eight epitopes from the M protein, and ten epitopes from each of the F and N proteins were predicted as linear epitopes. The surface accessibility method proposed seven surface epitopes from each of the H and F proteins in addition to six and four epitopes from the M and N proteins, respectively. For antigenicity, only two epitopes 142PPERV146 and 63DPLSP67 were predicted as antigenic from H and M, respectively. For T cells, MHC-I binding prediction tools showed multiple epitopes that interacted strongly with BoLA alleles. For instance, the epitope 45MFLSLIGLL53 from the H protein interacted with four BoLA alleles, while 276FKKILCYPL284 predicted from the M protein interacted with two alleles. Although F and N proteins demonstrated no favorable interaction with B cells, they strongly interacted with T cells. For instance, 358STKSCARTL366 from the F protein interacted with five alleles, followed by 340SQNALYPMS348 and 442IDLGPAISL450 that interacted with three alleles each. The epitopes from the N protein displayed strong interaction with BoLA alleles such as 490RSAEALFRL498 that interacted with five alleles, followed by two epitopes 2ATLLKSLAL10 and 304QQLGEVAPY312 that interacted with four alleles each. In addition to that, four epitopes 3TLLKSLALF11, 356YFDPAYFRL364, 360AYFRLGQEM368, and 412PRQAQVSFL420 interacted with three alleles each. Conclusion. Fourteen epitopes were predicted as promising vaccine candidates against PPRV from four immunogenic proteins. These epitopes should be validated experimentally through in vitro and in vivo studies.